Rainbow Connection Number of Prism and Product of Two Graphs - Darmawan, Randhi N.; Dafik, Dafik (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
An edge-colouring of a graph G is rainbow connected if, for any two vertices of G, there are k internally vertex-disjoint paths joining them, each of which is rainbow and then a minimal numbers of color G is required to make rainbow connected. The rainbow connection numbers of a connected graph G, denoted rc(G). In this paper we will discuss the rainbow connection number rc(G) for some special graphs and its operations, namely prism graph P_m,n, antiprism graph AP_n, tensor product of C_3 L_n, joint graph K_3+C_n.